A MODEL IMPLEMENTATION BALANCED SCORECARD IN THE RETAIL INDUSTRY - Iskhak, Iskhak; Purwana, Dedi; Handaru, Agung Wahyu; Wibowo, Setyo Ferry (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The purpose of this research is to identify in the literature the challenges and barriers to implementing the Balanced Scorecard in the retail industry. Previous research has mostly examined its application in the retail industry but did not explain in detail the challenges and obstacles in its application. Therefore, researchers evaluated the Balanced Scorecard framework in the retail industry into a model in the third-generation balanced scorecard framework by Kaplan & McMillan. This research uses systematic literature review to provide the right position in the direction of renewal into consideration regarding the challenges and obstacles companies face in implementing the Balanced Scorecard in the retail industry. This research finds that the retail category industry must be able to foster a culture of innovation and continuous improvement to take full advantage of the benefits of the Balanced Scorecard. This literature study still refers to the use of the classic Balanced Scorecard. It is hoped that future research will use at least the third-generation Balanced Scorecard is expected to use case studies and empirical research for further research and add measurement methods to evaluate the implementation of the balanced scorecard in s the retail industry.Keywords: Balance Scorecard, vision and strategy, retail industry